Increasing Trend of Pesticides’ Use in Vegetable Farming and Its Impact for Human Health: A case study of Bharatpur Metropolitan City, Nepal - Bhandari, Lila Raj (Nepal Journal of Multidisciplinary Research, 2019)
This study has analyzed the trend of pesticides' use in vegetable farming in third world country like Nepal, and its impact in public health. This study tries to find out the increasing trend of pesticides’ use in vegetable farming and its optimum impact in human health that has also focused for the protection of environmental and human health. Vegetable, a kind of cash crops, is the crops that millions and millions of people use as their meal and it is directly associated with human health, nutrition and daily consumption. Highly use of pesticides in vegetable farming is ultimately the poison for human being because of its maximum uses which is beyond the immunity power of the human beings. This is a sensitive issue that suffers thousands of children and old aged people by bringing acute and chronic diseases. This study moreover tries to juxtapose library and field-based information that directs it in particular way. Both, theory of production and health behavioral theory have been applied in this research because theory of production touches with the producers or farmers and health behavioral theory attaches with consumers. Economic growth model can be attached with the large scale of production. Production approach relates with producers that inspires them to produce large amount of vegetable. This study belongs to not only a field-based research, but it deals with library information, productive concepts and its impact on health too. Applying explorative research design, qualitative and quantitative method with primary and secondary sources of data, this study analyzed significantly statistical information and theoretical concepts. For this study, Bharatpur Metropolitan city (ward number 25 and 27) Nepal was chosen as a research area. In order to study the trend of pesticides use and its health impact, primary data were collected from the vegetable farmers who operate farming at the village area. A purposive sampling method was applied to collect data from 110 farmers who use pesticides in vegetable farming. Sample was drawn in such a way that all kinds of farmers might be included into the sample. Statistical tools such as percentage tables were used to analyze the data, and finding revealed that varieties of pesticides were used by farmers, but awareness associated with pesticides application was not found as we expected among the respondents. Although farmers showed favorable attitudes about the risks of pesticides uses, they did not use protective tools while applying pesticides. Less than half respondents (42.27%) have got primary education whereas only less than one third (30%) respondents have secondary level of education. 77.27% male and rest of the female for this study were selected. This study furthermore deals with the experience of the respondents which begins with 1 year to 30 years while 36.36% respondents have 11 to 15 years experiences in vegetable farming but only 9.09% respondents have 26-30 years experiences. More than two third majority (95.45%) respondents have given their view that pesticides are ultimately harmful for human health although it helps to increase the production. Air pollution, land pollution, and harmful to non-target organisms were also found from the study. Majority of the respondents (vegetable producers 27.27 percent) have opinioned that they were suffering from skin problems but 20.91 % respondents have expressed headache problems whereas 7.27 % had excessive sweating problems. Few of them have reported sneezing, vomiting, muscular difficulties, respiratory difficulties and trembling hands. In order to study the using trend and practice of pesticides, vegetable farmers were using different types of pesticides based on their decision. No proper advices from stakeholders and extension agent were taken, and no safety tools were used at the time of pesticides' application. Some had taken partial training associated with vegetable farming although strong practical knowledge was not found. Educational awareness, pest control, safe work habits, safety tools, policy, innovative method of farming, and organic farming are recommended for the policy maker from the study.